Coatings Systems: Chromium Carbide, Nitride and Carbonitride - Stela CONSTANTINESCU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science, 2005)
The process of the chemical deposition from vaporous implies the adsorption of the mobile atoms (monomers) on the substrate surface, their migration with embryos and stable nucleus formation, followed up by further growth through the adsorption of new atoms on the surface and also by the nucleus coalescence. The final structure of the deposed layer is given by various effects such as, the adsorption of impurities, the incorporation of gaseous, the co-deposition of another elements, the crystallization, etc. The ultimate properties of the coatings are further dependent on the nature and composition on the substrate. Therefore, in theory a vast number of substratecoating combinations is possible, with its own set of physical and chemical characteristics.